2004
DOI: 10.1074/jbc.m310041200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Per/Arnt/Sim (PAS) Domains to DNA Binding by the Basic Helix-Loop-Helix PAS Transcriptional Regulators

Abstract: The basic helix-loop-helix (bHLH) PAS transcriptional regulators control critical developmental and metabolic processes, including transcriptional responses to stimuli such as hypoxia and environmental pollutants, mediated respectively by hypoxia inducible factors (HIF-␣) and the dioxin (aryl hydrocarbon) receptor (DR). The bHLH proteins contain a basic DNA binding sequence adjacent to a helix-loop-helix dimerization domain. Dimerization among bHLH.PAS proteins is additionally regulated by the PAS region, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
72
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 40 publications
10
72
1
3
Order By: Relevance
“…5c). These findings not only suggest that the PASB domain is capable of initiation of dimerization and that the PASA domain is necessary for successful completion of this process (resulting in Hsp90 displacement), but are also consistent with the previously reported inhibitory effect of the PASB domain on transformation (16,18) and demonstration of PASA as a major contributor to the stability of the AhR:Arnt dimer (14). Moreover, it has been found that a conformational change in the AhR is required for stable dimer formation because geldanamycin-or salt-mediated dissociation of Hsp90 from the AhR resulted in less stable dimer formation (5,13).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…5c). These findings not only suggest that the PASB domain is capable of initiation of dimerization and that the PASA domain is necessary for successful completion of this process (resulting in Hsp90 displacement), but are also consistent with the previously reported inhibitory effect of the PASB domain on transformation (16,18) and demonstration of PASA as a major contributor to the stability of the AhR:Arnt dimer (14). Moreover, it has been found that a conformational change in the AhR is required for stable dimer formation because geldanamycin-or salt-mediated dissociation of Hsp90 from the AhR resulted in less stable dimer formation (5,13).…”
supporting
confidence: 77%
“…Although the PASA domain is essential for formation of the stable AhR:Arnt dimer, the PASB domain contains a ligand binding site and one of the Hsp90 binding sites (6,14,15). The PASB domain has been suggested to exert an inhibitory effect on AhR transformation and its deletion results in an AhR that is constitutively active with respect to its transformation/DNA binding and transcriptional activation functions (16 -18).…”
mentioning
confidence: 99%
“…ARNT constitutively dimerizes with other bHLH-PAS family members that themselves are regulated, including AHR and hypoxia-inducible factors (HIFs). PAS domains are essential for stable heterodimer formation, as supported by biochemical studies that show that deletion of PAS domains from ARNT (12,13) or its partners [e.g., HIF-2␣ (14)] impairs the formation and activity of regulatory complexes. Biophysical studies of PAS domains from HIF-2␣ and ARNT have shown that the C-terminal PAS-B domains from these proteins bind each other via an antiparallel ␤-sheet-␤-sheet packing (15,50).…”
mentioning
confidence: 91%
“…bHLH-PAS heterodimers are dependent on intersubunit contacts between the basic bHLH and tandem PAS domains (2)(3)(4). The second of two PAS domains, PAS-B, plays a critical role in maintaining the stability of this complex, given that mutations in HIF-2α PAS-B disrupt HIF-α/ARNT interactions and decrease transactivation in vivo (3,4).…”
Section: Transcriptional Coactivators | Protein/protein Interactions mentioning
confidence: 99%